O estágio supervisionado no curso de pedagogia - Medeiros, Denise Rosa (Universidade do Vale do Rio dos Sinos, 2013)
The present research qualitative methodological perspective has aimed at contributing to the initial training of teachers. Has a special focus on the role of the supervised internship in course curriculum of pedagogy. Explores the perception of teachers, students and coordinators of the course on the topic, especially addressing the relationship between theory and practice in theinitial training of teachers, Curricular guidelines arising from the law of Guidelines and Bases of Brazilian education, promulgated in 1996. Takes four universities in the State of Santa Catarina, Brazil, as dialogue. The intention was toreflect on the initial proposal in the courses of pedagogy, especially from the place built for the supervised internship, where explicit exponentially, the relation theory and practice, being of significant importance in the training of future teachers. The study was conducted with the empirical corpus semi-structured interviews with te achers and coordinators and questionnaires with open and closed questions with students of pedagogy. The data were analyzed based on content analysis from Bardin (2009). Information collected were organized into dimensions that describe the perceptions of teachers, coordinators and students, based on knowledge of the supervised internship. The study involved the analysis of official documents as well as Pedagogical Political project of the courses of pedagogy and institutionsin focus in this research. The theoretical availed of contributions, mostly from Freire (1992, 2000), Nóvoa (1997, 2002), Pimenta (2002), Libâneo (2002), Piconez (1998), Brzezinski (1996), among others. The results showed the importance of participatory and collective process of construction of Educational Projects committed to the school context, with the relationship between knowledge, with an emphasis oninterdisciplinarity, and with the reflexive condition to face the complexity of teaching profession in contemporary times. The data reinforced the understanding that the internship is an articulator of the curriculum and the relationship theory and practice, regarded as learning space of the profession in the University's partnership with schools of basic education. There is, still, inferences for the improvement of procedures for the training, including curriculum issues and pedagogical practice developed in the courses.
Keywords: Estágio supervisionado; Teoria e prática pedagógica; Formação de professores; Curso de pedagogia; Supervised internship; Pedagogical theory and practice; Teacher training; Course in pedagogy; ACCNPQ::Ciências Humanas::Educação